Atrial functional mitral regurgitation: A cautionary tale?. Issue 1 (12th July 2022) - Inci, Errol; Block, Peter C.
Keypoints: Approximately one‐third of patients with functional mitral regurgitation (FMR) have atrial FMR (A‐FMR) and need to be identified. Transcatheter edge to edge repair (TEER) may benefit patients with A‐FMR. Many unknowns remain concerning A‐FMR and TEER which require further investigation.